Longitudinal Study of the Effect of Clean and Healthy Living Behaviour (PHBS) on the Incidence of Communicable Diseases in Urban Environments - Sukmawati; Sri Hazanah (CV. Get Press Indonesia, 2025)
The aim of this study was to evaluate the long-term impact of Clean and Healthy Living Behavior (PHBS) implementation on the incidence of infectious diseases in urban environments. Methods. This study used a quantitative approach with a longitudinal study design. Data collection was conducted through a validated questionnaire survey, direct observation, and in-depth interviews with respondents. Data analysis was conducted using inferential statistical methods, including logistic regression to identify the association between PHBS categories and disease incidence. Results. Overall, 31.7% of respondents experienced at least one type of infectious disease during the study period. ARI was the most common infectious disease (18.3%), followed by diarrhoea (6.7%), dengue haemorrhagic fever (DBD) (4.2%), and tinea (2.5%). The results of bivariate analysis and logistic regression revealed that there was a significant relationship between the implementation of clean and healthy living behavior and the incidence (p = 0.001). Response to infectious diseases was 70% lower in the group with good compared to those with poor (OR = 0.30; p = 0.0.001). Conclusions. The implementation of good clean living behavior can significantly reduce the risk of infections in urban environment.